2010
DOI: 10.4103/0973-1482.77085
|View full text |Cite
|
Sign up to set email alerts
|

Extent of surgery in the management of phyllodes tumor of the breast: A retrospective multicenter study from India

Abstract: The unpredictable behavior of histological types and the disputable results of particular surgical procedures have contributed to the controversies. The therapeutic issue is further compounded by an imprecise preoperative diagnosis. This study shows that wide local excision for benign and borderline and simple mastectomy with or without reconstruction for the malignant PT of the breast are acceptable best surgical options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
2
4
1
Order By: Relevance
“…The phyllodes tumor patients enrolled in this study were younger than expected. In previous studies, it has been reported that patients with borderline/malignant phyllodes tumors were older than those with benign phyllodes tumors (3,4). In this study, it was detected that the borderline/malignant phyllodes tumor patients also had more advanced age.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The phyllodes tumor patients enrolled in this study were younger than expected. In previous studies, it has been reported that patients with borderline/malignant phyllodes tumors were older than those with benign phyllodes tumors (3,4). In this study, it was detected that the borderline/malignant phyllodes tumor patients also had more advanced age.…”
Section: Discussionsupporting
confidence: 61%
“…The assumption that phyllodes tumors may be affected by hormonal milieu suggest a relationship between these types of tumors and menopausal status. However, in both previous reports and the current study a significant association was not detected between the histopathological subtype of phyllodes tumor and menopausal status (3). Phyllodes tumors, similar to breast cancer, are often seen in women.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…PTs spread hematogenously. The rate of axillary metastasis is low (0%-2%) and therefore routine axillary examination is not recommended (8,22). However, axillary examination can be performed in aggressive tumors with a diameter greater than 5 cm and high mitotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mastectomy should be reserved for special indications such as local recurrence, gross tumors (>10 cm), inappropriate tumor-breast ratio, and cases in which tumor-free surgical margins are impossible to be achieved. The excisions must be carried out with the effort to obtain at least a 1 -2 cm tumor-free distance from the surgical margins (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In their study, Mangi et al20 reported that this distance was less than 1 cm in all cases of local recurrences, and De Roos et al (22) stated that all local recurrences were the outcomes of insufficient primary surgery having left positive surgical margins in the initial operations.…”
Section: Surgical Treatmentmentioning
confidence: 99%